Ecological Transition and Circular Economy - Raimo, Nicola; Vitolla, Filippo; Malandrino, Ornella; Esposito, Benedetta (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint contributes to the debate on the Ecological Transition and Circular Economy from a multidimensional perspective. Research from several scientific fields has been developed, providing a comprehensive picture of the complexity of the circular transition. Indeed, the reprint highlights how creating a functioning circular economy requires combining different knowledge, skills, perspectives and approaches to shift towards sustainable consumption and production patterns successfully. Special attention is given to the multiple dimensions of circular economy applications, with articles focused on different circular economy application levels, such as processes, companies, supply chains, and cities. Furthermore, the reprint explores in detail how a circular economy becomes applied to the energy, construction and agri-food sectors that are particularly committed to this circular transition.